Plan de exportación de banano de la hacienda el recuerdo de la provincia de El Oro - Cedillo Decker, Daniela Ramón (2015)
This work is done by titration in order to perform an analysis of the process of exporting bananas from the plantation "El Recuerdo" to the niche market of Canada from Bourbon province of El Oro, giving it a more competitive approach for the production of this estate; as our bananas in Ecuador has a very important role in the economy and the country's development, from the social and economic points of view, total GDP is 3.84% in the banana participates in recent times, generating foreign exchange, social, creates many jobs, especially in the Ecuadorian coast where is concentrated the largest banana production of the country; our country has advantages over competing countries, thanks to its climate and fertile land, identically, disadvantages such as price volatility, despite having an official price regulating the market, which is not executed in the country, the instability of world prices by the economic crisis we are experiencing, however Ecuadorian bananas is known for its high level of quality, which is why Ecuador is known as the banana capital of the world, followed by Costa Rica , the Philippines and Colombia, the European Union and its main exporter. In the first part of the work rules and market access approaches with a series of references based on scientific journals that support the work performed it is presented. The second chapter discloses the description of the proposal in which the structural components are given a brief overview of the company, the objectives to be achieved, and information necessary for the inclusion of bananas in a target market. In chapter three the project analyzed the effect it has on the social, environmental and economic spheres. The North American market is a market for its proximity makes it conducive to our country to cut travel costs of fruit, considering that the demand for bananas in the world according to studies by the FAO, the projections world import demand for this fruit will increase by 1.9% annually for this study was conducted of the Canadian market, which is in itself a good consumer of this musacea, for its nutritional qualities, is why he makes the procedures for processing fruit export this northern market, managing to have a higher income for the El memory.